2009
DOI: 10.1148/radiol.2501072153
|View full text |Cite
|
Sign up to set email alerts
|

Can Cortical Thickness Asymmetry Analysis Contribute to Detection of At-Risk Mental State and First-Episode Psychosis?: A Pilot Study

Abstract: Purpose:To investigate whether cortical thickness analysis in individuals with an at-risk mental state (ARMS) might contribute to early detection of psychosis. Materials and Methods:Ethics committee approval and written informed consent were obtained. Cortical thickness was analyzed because early disease-related morphometric changes were expected to be most pronounced in the cerebral cortex. With the assumption of progressive change in cortical thickness from control subjects, to those with an ARMS, and then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 31 publications
4
53
0
2
Order By: Relevance
“…Our findings in patients are consistent with previous neuroimaging reports from the same sample (Borgwardt et al, 2007aHaller et al, 2009) and similar to other ARMS samples (Velakoulis et al, 2006;Meisenzahl et al, 2008), as well as longitudinal MRI studies using voxel-based morphometry methods, where progressive volumetric reductions in hippocampal and parahippocampal regions were found in those ARMS subjects that made a transition to psychosis . Furthermore, also the finding that non-converters (ARMS-NT) compared to converters (ARMS-T) did not differ in left or right HVs is well in line with previous VBM studies of ARMS (Borgwardt et al, 2007a;Meisenzahl et al, 2008.…”
Section: Arms-nt)supporting
confidence: 93%
“…Our findings in patients are consistent with previous neuroimaging reports from the same sample (Borgwardt et al, 2007aHaller et al, 2009) and similar to other ARMS samples (Velakoulis et al, 2006;Meisenzahl et al, 2008), as well as longitudinal MRI studies using voxel-based morphometry methods, where progressive volumetric reductions in hippocampal and parahippocampal regions were found in those ARMS subjects that made a transition to psychosis . Furthermore, also the finding that non-converters (ARMS-NT) compared to converters (ARMS-T) did not differ in left or right HVs is well in line with previous VBM studies of ARMS (Borgwardt et al, 2007a;Meisenzahl et al, 2008.…”
Section: Arms-nt)supporting
confidence: 93%
“…People at high risk of psychosis show qualitatively similar volumetric abnormalities to patients with schizophrenia. Cortical brain abnormalities have been found in genetically defined high-risk populations such as first-degree relatives and co-twins of patients with schizophrenia, as well in people with ARMS [13,[68][69][70][71][72][73][74][75][76][77][78][79][80]. Previous longitudinal MRI studies in this group found that the subset of patients who developed psychosis showed a longitudinal reduction in GM in the orbito-frontal, temporal lobe, parietal lobe and cerebellum [79,81,82].…”
Section: Effects Of Antipsychotic Medication On Structural Neuroimagimentioning
confidence: 82%
“…We performed a paired t test for all of these re gions for each group (CUD, NCUD, control) separately. 45 …”
Section: Discussionmentioning
confidence: 99%